Testing and balancing HVAC air and water systems - Monger, Sam 1946- (Fairmont press, 1990)
Every aspect of testing, adjusting and balancing HVAC systems is addressed in this text, and details of all major components are provided. All needed equations and a variety of conversions are also supplied.